CASA, the Common Astronomy Software Applications for Radio Astronomy. (1st November 2022) - The CASA Team,; Bean, Ben; Bhatnagar, Sanjay; Castro, Sandra; Meyer, Jennifer Donovan; Emonts, Bjorn; Garcia, Enrique; Garwood, Robert; Golap, Kumar; Villalba, Justo Gonzalez; Harris, Pamela; Hayashi, Yohei; et al.
Abstract: CASA, the Common Astronomy Software Applications, is the primary data processing software for the Atacama Large Millimeter/submillimeter Array (ALMA) and the Karl G. Jansky Very Large Array (VLA), and is frequently used also for other radio telescopes. The CASA software can handle data from single-dish, aperture-synthesis, and Very Long Baseline Interferometery (VLBI) telescopes. One of its core functionalities is to support the calibration and imaging pipelines for ALMA, VLA, VLA Sky Survey, and the Nobeyama 45 m telescope. This paper presents a high-level overview of the basic structure of the CASA software, as well as procedures for calibrating and imaging astronomical radio data in CASA. CASA is being developed by an international consortium of scientists and software engineers based at the National Radio Astronomy Observatory (NRAO), the European Southern Observatory, the National Astronomical Observatory of Japan, and the Joint Institute for VLBI European Research Infrastructure Consortium (JIV-ERIC), under the guidance of NRAO.